2010
DOI: 10.1016/j.vetpar.2010.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plasmodium relictum causing mortality in penguins (Spheniscus magellanicus) from São Paulo Zoo, Brazil

Abstract: This study reports avian malaria caused by Plasmodium relictum in Magellanic Penguins (Spheniscus magellanicus) from São Paulo Zoo. The disease was highly infective among the birds and was clinically characterized by its acute course and high mortality. The penguins of São Paulo Zoo were housed for at least 2 years without malaria; however, they had always been maintained in an enclosure protected from mosquito exposure during the night period. When they presented pododermatitis, they were freed at night for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
90
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 22 publications
5
90
0
6
Order By: Relevance
“…(Pereira et al 2009) in blood smears. Another study in Brazil reported the presence of malaria in Spheniscus magellanicus at the São Paulo zoo (Bueno et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pereira et al 2009) in blood smears. Another study in Brazil reported the presence of malaria in Spheniscus magellanicus at the São Paulo zoo (Bueno et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of parasites in blood smears is still the routine diagnostic method, but may present a low sensitivity rate and is a cumbersome procedure (Perkins & Schall 2002, Belo 2007 (Griner 1974, Fix et al 1988, Brossy et al 1999, Levin et al 2009, Bueno et al 2010, Dinhopl et al 2011. Graczyk et al (1994), in search of Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Internationally, avian malaria is a known cause of mortality in captive penguins kept in outdoor displays or zoos with P. relictum and P. elongatum being the associated parasites. [6][7][8][9][10] In the case of wild birds, P. tejerai, P. cathemerium, P. nucleophilum and P. unalis could be identified in Magellanic penguins (S. magellanicus) undergoing rehabilitation along the coast of Brazil. 11 The first report of a Plasmodium infection in an African penguin in the wild was from Saldanha Bay, described as P. relictum subsp.…”
Section: Introductionmentioning
confidence: 99%
“…2011), especially in cases where a host encounters a novel parasite (e.g., Atkinson and Samuel 2010; Bueno et al. 2010). Oceanic archipelagos are often considered isolated and potentially more protected from natural colonization by novel pathogens and parasites.…”
Section: Introductionmentioning
confidence: 99%